Steps In Human Resource Planning - Manalu, Hosanna Agree Rosion; Ali, Fajri Alfisyahri; Sonawi, Sonawi; Supratikta, Hadi (JAKI : Jurnal Akuntansi, 2024)
Human Resources (HR) planning is a strategic process that aims to ensure the availability of the right workforce in quantity and quality according to the organization's current and future needs. This article discusses the main steps in HR planning, from analyzing the organizational situation to implementing HR strategies. The first step is an analysis of the internal and external environment, which involves identifying factors that influence workforce needs, such as changes in technology, regulations, and labor market trends. Second, projections of human resource needs are carried out by estimating the number, skills and competencies of the workforce required in the future. Third, analyze the availability of internal and external labor to identify gaps between labor demand and supply. Fourth, formulating strategies for managing HR gaps, such as recruitment, training, development and retention programs. Fifth, implementation and evaluation of the HR plan, which includes implementing the designed strategy as well as monitoring and adjusting the plan according to changing organizational needs. This article emphasizes the importance of a systematic and integrated approach in HR planning to support the achievement of organizational strategic goals.